Prenatal factors in the aetiology of testicular cancer: an epidemiological study of childhood testicular cancer deaths in Great Britain, 1953-73. - Swerdlow, A J (1982)
A case-control study is reported based on 87 deaths from testicular cancer that occurred in children in Great Britain 1953-73. Factors that significantly increased relative risk were tuberculosis of the mother during the index pregnancy and maternal epilepsy; factors that increased risk but not significantly were hyperemesis in the index pregnancy, a maternal history of stillbirths, and hernia and genitourinary defects in the child. Cryptorchidism was not studied. The available evidence suggests that prenatal determinants of testicular cancer in adults are also determinants of testicular cancer in childhood. The incidence and mortality from this disease are not increasing among children in Britain and other countries, whereas there is an increasing trend in young adults in several developed countries. Probably, therefore, the secular increase in the rates of young adult testicular cancer is due to factors that affect adults but not children, the hence are likely to be postnatal.